2012
DOI: 10.1590/s0124-00642012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Qualidades físicas de atletas e praticantes de Ginástica Rítmica pré e pós-púberes

Abstract: Significant statistical differences were found between the different categories in regarding the all the variables between the different categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…Thus, Miletić, Sekulic, et al (2004)found lower values in the VTJ test (21.2±4.4cm) in younger gymnasts (7.1±0.3 years). Menezes et al (2012) observed higher values than in our study: 35.1±3.5cm, 38.0±4.3cm and 40.1±2.7cm, respectively at state, national and international levels. Further, the authors verified that the gymnasts, who had already menstruated, presented higher results in the vertical jump.…”
Section: Dicussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Thus, Miletić, Sekulic, et al (2004)found lower values in the VTJ test (21.2±4.4cm) in younger gymnasts (7.1±0.3 years). Menezes et al (2012) observed higher values than in our study: 35.1±3.5cm, 38.0±4.3cm and 40.1±2.7cm, respectively at state, national and international levels. Further, the authors verified that the gymnasts, who had already menstruated, presented higher results in the vertical jump.…”
Section: Dicussioncontrasting
confidence: 83%
“…Finally, the elite (34.1±2.9 cm) and 1 st division (34.5±5.5 cm) gymnasts presented a higher lower limbs' explosive strength level than base gymnasts (31.1±4.8 cm), according to the results achieved in the VTJ test. The vertical jump is widely used in the different elements in RG (Menezes, Novaes, & Fernandes-Filho, 2012),so, several previous research resorted to different devices to evaluate the vertical jump of gymnasts (Del Vecchio et al, 2014;Donti et al, 2016;H. Douda et al, 2008;Gateva, 2011Gateva, , 2013Grigoroiu, Pelin, Netolitzchi, & Pricop, 2015;Kritikou et al, 2017;Menezes & Fernandes Filho, 2006;Miletić, Katić, et al, 2004;Miletić, Sekulic, et al, 2004;Román et al, 2012;Rutkauskaitė & Skarbalius, 2009, 2011Silva et al, 2016;Stadnik et al, 2010).…”
Section: Dicussionmentioning
confidence: 99%
“…Among the instruments used, we must underline the trigonometric method (Irurtia et al, 2010), measuring tape (Leyton et al, 2012), goniometer (360º) (De Souza et al, 2012), dimensionless method consisting in comparison of joint ROM to an assessment scale (Batista et al, 2015;Batista et al, 2019), code of points and posture analysis through video recording (Boligon et al, 2015), manual goniometer (Fraga et al, 2018), Kinovea, specific software for 2D movement analysis (Ferri-Caruaca et al, 2020), and cameras or camcorders in the rest of studies that used degrees or longitudinal measurements (cm).…”
Section: Instruments and Measurementsmentioning
confidence: 99%
“…Research conducted by Menezes et al (2012), Melin et al (2015) and Zaccagni et al (2019) highlights that RG tend to overestimate aesthetics, focusing on achieving a very low-fat percentage in order to improve aesthetic performance. This can negatively affect health, potentially leading to low energy availability for performance, which increases the risk of injury (De Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%